Sutureless Aortic Valve Prosthesis in Redo Procedures: Single-Center Experience - Alina Zubarevich; Eleftherios T. Beltsios; Arian Arjomandi Rad; Lukman Amanov; Marcin Szczechowicz; Arjang Ruhparwar; Alexander Weymann (Medicina, 2023)
Background and Objectives: Sutureless aortic valve prostheses have presented favorable hemodynamic performance while facilitating minimally invasive access approaches. As the population ages, the number of patients at risk for aortic valve reoperation constantly increases. The aim of the present study is to present our single-center experience in sutureless aortic valve replacement (SU-AVR) in reoperations. Materials and Methods: The data of 18 consecutive patients who underwent SU-AVR in a reoperation between May 2020 and January 2023 were retrospectively analyzed. Results: The mean age of the patients was 67.9 ± 11.1 years; patients showed a moderate-risk profile with a median logistic EuroSCORE II of 7.8 (IQR of 3.8–32.0) %. The implantation of the Perceval S prosthesis was technically successful in all patients. The mean cardiopulmonary bypass time was 103.3 ± 50.0 min, and the cross-clamp time was 69.1 ± 38.8 min. No patients required a permanent pacemaker implantation. The postoperative gradient was 7.3 ± 2.4 mmHg, and no cases of paravalvular leakage were observed. There was one case of intraprocedural death, while the thirty-day mortality was 11%. Conclusions: Sutureless bioprosthetic valves tend to simplify the surgical procedure of a redo AVR. By maximizing the effective orifice area, sutureless valves may present an important advantage, being a safe and effective alternative not only to traditional surgical prostheses but also to transcatheter valve-in-valve approaches in select cases.